Glucocorticoid-Induced TNFR-Related (GITR) Protein and Its Ligand in Antitumor Immunity: Functional Role and Therapeutic Modulation - Theresa Placke; Hans-Georg Kopp; Helmut Rainer Salih (Clinical and Developmental Immunology)
The ability of the tumor necrosis factor receptor (TNFR) family member GITR to modulate immune responses has been the subject of multiple studies. Initially thought to be critically involved in governing functions of regulatory T cells, GITR and its ligand GITRL have meanwhile been found to modulate the reactivity of various different cell types and to influence a broad variety of immunological conditions including the immune response against tumors. Not only GITR, but also GITRL is capable of transducing signals, and the consequences of GITR-GITRL interaction may vary among different effector cell types, differ upon signal transduction via the receptor, the ligand, or both, depend on the level of an ongoing immune response, and even differ among mice and men. In this paper, we address available data on GITR and its ligand in immune responses and discuss the role and potential therapeutic modulation of this molecule system in antitumor immunity.